2004
DOI: 10.1590/s0021-75572004000800013
|View full text |Cite
|
Sign up to set email alerts
|

Morbidade respiratória no primeiro ano de vida de prematuros egressos de uma unidade pública de tratamento intensivo neonatal

Abstract: Objective: The objective of this study was to verify the incidence of respiratory morbidity in the first year of life in very low birth weight preterm infants and also to compare the presence of respiratory morbidity in the first year of life according to neonatal risk factors.Methods: This is a prospective cohort study. We studied preterm newborn infants weighing less than 1,500 g and with gestational age less than 34 weeks who were born between 1998 and 2000. During the first year of life, the infants receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
12

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 20 publications
(34 reference statements)
0
20
0
12
Order By: Relevance
“…However, it was observed that more than two thirds of home environments surveyed had medium or high level of stimulation in AHEMD-Total and good or very good opportunities in the dimensions of variety (if the child plays with other children, if choose their toys, if games are stimulated by parents, type of clothing to play, and the time it remains in certain environments) and inner space (presence of apparatuses, internal surfaces and internal space for existing games at home). Opportunities for home environment stimuli are the main catalysts of learning to many children, for being the location where they spend most of the time and allow the experience of different sensorimotor experiences 23,24 . Thus, it seems that participants had favorable conditions for development of functional mobility skills, which reflected in their performance, which remained within the normal range (PEDI normative score).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was observed that more than two thirds of home environments surveyed had medium or high level of stimulation in AHEMD-Total and good or very good opportunities in the dimensions of variety (if the child plays with other children, if choose their toys, if games are stimulated by parents, type of clothing to play, and the time it remains in certain environments) and inner space (presence of apparatuses, internal surfaces and internal space for existing games at home). Opportunities for home environment stimuli are the main catalysts of learning to many children, for being the location where they spend most of the time and allow the experience of different sensorimotor experiences 23,24 . Thus, it seems that participants had favorable conditions for development of functional mobility skills, which reflected in their performance, which remained within the normal range (PEDI normative score).…”
Section: Discussionmentioning
confidence: 99%
“…According to Mello, Dutra and Lopes 23 , respiratory disorders are common in premature infants and are important factor for mortality and morbidity in childhood, accounting for recurrent hospitalizations in the first years of life. It is common to observe that most of parents, in order to avoid the disease exacerbation, have excess care, leading to a sort of limitation on motor experiences that can impair the process of developing and refining the functional abilities 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A rotina de acompanhamento das crianças durante o primeiro ano de vida foi mensal 8,9 , as informações referentes ao período (variáveis só-cio-demográficas, maternas, neonatais e pós-neonatais) foram publicadas previamente 7,8,9 enquanto o acompanhamento, a partir de 12 meses de vida, se caracterizou por consultas trimestrais. A cada consulta trimestral realizada eram coletadas as fichas com registros dos responsáveis sobre a presença de intercorrências respiratórias ocorridas desde a última consulta até a consulta atual, portanto, se a consulta ocorreu no trimestre imediatamente anterior, o registro seria referente a um período de observação de três meses.…”
Section: Materiais E Métodosunclassified
“…Fatores como: uso de ventilação mecânica, pneumonia neonatal e alteração na função pulmonar apresentaram importante repercussão na incidência de morbidade respiratória no primeiro ano de vida de crianças nascidas prematuras 7,8,9 , porém no nosso meio ainda é pouco conhecido se a morbidade respiratória nessas crianças se ARTIGO ARTICLE mantém elevada e se tal associação se mantém relevante em relação à morbidade respiratória na infância, entre 1 e 3 anos de vida.…”
Section: Introductionunclassified
“…A displasia broncopulmonar (DBP) ainda é a morbidade mais comum em recém-nascidos (RN) de extremo baixo peso, embora a incidência, os fatores de risco e a gravidade dessa doença tenham se modificado substancialmente após a introdução de novas terapias e técnicas de ventilação mecânica [1][2][3] . Sua patogênese é multifatorial e inclui imaturidade, infecção, baro/volutrauma e toxicidade pelo uso do oxigênio.…”
Section: Introductionunclassified